Strategi BUMDes Dalam Pengembangan Pariwisata Di Wisata Bahari Tlocor - Hafit, Hafit Wahyu Ramadhan; Hendra Sukmana, Hafit Wahyu Ramadhan (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2023)
The purpose of this research is to analyze and describe the BUMDES Strategy in Tourism Development at Tlocor Marine Tourism, Jabon District, Sidoarjo Regency, in order to find out the problems in tourism development through the role of government, managers. The approach taken in this research is a qualitative descriptive approach by conducting interviews, observation and documentation. The results of this study indicate that, first, the objectives carried out by BUMDES in tourism development at Tlocor Marine Tourism have been fulfilled and are running well because they have a significant impact on the community's economy, especially for the Tlocor Hamlet Community. Second, the surrounding community environment is very supportive and plays an active role with the development of tourism in Tlocor Marine Tourism. This is evidenced by the community fully participating in the development of facilities and infrastructure in the tourist area and maintaining the surrounding environment so that it is more beautiful and maintained. Third, the actions that have been taken by BUMDES and also POKDARWIS as managers in Tlocor Marine Tourism have been going well. This can be seen with several strategic efforts that continue to be carried out by BUMDES and also POKDARWIS as well as layers of society that support development such as by collaborating by holding tour packages with other tourism stakeholders, besides that the development of facilities and infrastructure continues to be developed to attract tourists and as the progress of tourism.